2008
DOI: 10.1080/00207140701849486
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Hypnotic-Analgesia Treatment for Chronic Pain in Persons with Disabilities

Abstract: Data from 26 participants in a case series of hypnotic analgesia for chronic pain were examined to determine the long-term effects of hypnosis treatment. Statistically significant decreases in average daily pain intensity, relative to pretreatment values, were observed at posttreatment and at 3- and 9-month follow-up but not at 6- or 12-month follow-up. The percent of participants who reported clinically meaningful decreases in pain were 27%, 19%, 19%, and 23%, at the 3-, 6-, 9-, and 12-month follow-up points,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…34,35 Specifically, our post-treatment percentage of patients who reported significant improvements ranged from 31 to 33.3% (Table 3), which is similar to results of the other study that reported a clinically significant post-treatment improvement percentage of 35%. 34,35 Nevertheless, in our study, the percentage of patients treated with hypnosis who reported clinically significant improvement ranged from 17.2 to 19.2% at the 3-month follow-up, and from 27.6 to 34.8% at the 6-month follow-up (Table 3). These percentages were different than those reported in the previously mentioned study 35 that were 27% at 3-month follow-up and 19% at the 6-month follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…34,35 Specifically, our post-treatment percentage of patients who reported significant improvements ranged from 31 to 33.3% (Table 3), which is similar to results of the other study that reported a clinically significant post-treatment improvement percentage of 35%. 34,35 Nevertheless, in our study, the percentage of patients treated with hypnosis who reported clinically significant improvement ranged from 17.2 to 19.2% at the 3-month follow-up, and from 27.6 to 34.8% at the 6-month follow-up (Table 3). These percentages were different than those reported in the previously mentioned study 35 that were 27% at 3-month follow-up and 19% at the 6-month follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…10,16,21,34,41,44,[56][57][58][73][74][75] In FM in particular, CBT has been proven effective at producing modest outcomes across multiple domains, including pain, fatigue, physical functioning, and mood, 4,7,23,24,26,28,32,64,72,77 even when it is provided in a group format. 38,77 Nevertheless, some authors have questioned the usefulness of CBT in the treatment of some key symptoms of FM, such as pain, fatigue and sleep disturbances.…”
mentioning
confidence: 99%
“…The pre-post study showed that some participants continued using self-hypnosis techniques even at 1-year follow-up. 23 Jensen et al 33 supported this finding in a study involving patients with SCI and multiple sclerosis. The study indicated that although 81% of the participants continued the use of hypnosis at 1-year follow-up, only 23% had a clinically significant reduction in pain intensity.…”
Section: Hypnosissupporting
confidence: 73%
“…Obviously, self-reported likes and dislikes are insufficient to conclude with certainty that hypnosis increases the quality of support and improves post-surgical recovery, but the present results are consistent with such possibilities. 20,21 This report underlines the relatively high level of acceptance of a hypnotic intervention for managing pain and anxiety during pregnancy termination. Women indicated that they would recommend hypnosis and reported advantages particularly in the better accompaniment provided and the improved recovery.…”
Section: Discussionmentioning
confidence: 78%